Optimalisasi E-Bisnis Untuk Emisi Karbon Rendah Dan Keberlanjutan - Wahid, Deden Abdul; Yuliaty, Farida (Yayasan Cendekia Gagayunan Indonesia, 2025)
This study focuses on optimizing e-business to reduce carbon footprint and promote environmentally friendly products as part of business sustainability efforts. The purpose of the study is to analyze the strategy of integrating green technology and digital-based marketing approaches in e-business to address global environmental challenges. The method used involves literature studies and empirical data analysis related to the use of renewable energy-based data centers, operational migration to cloud computing, and the effectiveness of promoting environmentally friendly products through digital platforms. The results of the study indicate that the application of green technology, such as renewable energy-based data centers and migration to cloud computing, can significantly reduce energy consumption and reduce carbon emissions. In addition, the promotion of environmentally friendly products increases consumer awareness and business competitiveness in the global market. The conclusion of this study confirms that the synergy between green technology and integrated marketing strategies can support the sustainability of e-business operations while contributing to solutions to global environmental challenges. These findings provide practical guidance for business actors to create added value and competitiveness through the adoption of environmentally friendly technology and marketing strategies.